Syntheses and properties of 2,4- dichlorophenoxyacetate-layered double hydroxide-nanocomposites at different molar ratio of Mg-Al by co-precipitation method - Yahaya, Asmah; Hussein, Mohd Zobir; Zainal, Zulkarnain; Mohamad Jaafar, Adila (Universiti Putra Malaysia Press, 2005)
﻿Dichlorophenoxyacetate-Mg-Al-layered double hydroxide (MADs) were prepared by spontaneous self-assembly technique with different Mg-Al molar ratio. PXRD patterns of the materials show that the basal spacing expanded from 8.0 Ǻ -8.9 Ǻ in the Mg-Al-layered double hydroxide with nitrate as the counter anion to 22.2 Ǻ – 23.1 Ǻ in the nanocomposite to accommodate the 2,4-D anion. FTIR studies show that the absorption bands of the resulting nanocomposite materials correspond to the characteristic of both the 2,4-D and the Mg-Al-layered double hydroxides. Intercalation of 2,4-D into the interlayer of Mg-Al-layered double hydroxides were confirmed by the strong agreement in the results of PXRD, FTIR and elemental analyses. TGA-DTG analyses show that the intercalation of the 2,4-D anion in the layered double hydroxide inorganic interlayer increased the thermal stability. The resulting layered double hydroxides and nanocomposites show Type IV adsorption-desorption isotherms indicating the mesoporous structure of the material. BET surface area and BJH desorption average pore diameter was found to be altered after the intercalation process took place. Scanning electron micrographs of MALs and MADs showed that both materials have similar agglomerates of compact and non-porous structure surface morphology.